2005
DOI: 10.1080/00015550510030087
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the Probability of the Evolution of Parapsoriasis en Plaques into Mycosis Fungoides

Abstract: Parapsoriasis en plaque has been suggested to be an early manifestation of mycosis fungoides (cutaneous T-cell lymphoma). We explored the disease course of patients with small plaque or large plaque parapsoriasis in a 26-year retrospective cohort analysis of 105 parapsoriasis patients, who were clinically and histopathologically followed up in Helsinki and Tampere University Hospitals. Eventual later cancers of these patients were verified from the Finnish Cancer Registry. In the small plaque parapsoriasis gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 22 publications
3
32
0
2
Order By: Relevance
“…A consistent viral, environmental, or occupational causative factor or hereditary mutation has not been found (Ranki et al, 1990;Väkevä et al, 2000Väkevä et al, , 2005Burg et al, 2001;Girardi, 2004 review;Morozov et al, 2005;Pawlaczyk et al, 2005). Early conventional cytogenetic studies showed a large repertoire of chromosomal abnormalities in CTCL, both clonal and non-clonal, but no specific abnormality (Whang-Peng et al, 1982).…”
Section: Etiology General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…A consistent viral, environmental, or occupational causative factor or hereditary mutation has not been found (Ranki et al, 1990;Väkevä et al, 2000Väkevä et al, , 2005Burg et al, 2001;Girardi, 2004 review;Morozov et al, 2005;Pawlaczyk et al, 2005). Early conventional cytogenetic studies showed a large repertoire of chromosomal abnormalities in CTCL, both clonal and non-clonal, but no specific abnormality (Whang-Peng et al, 1982).…”
Section: Etiology General Remarksmentioning
confidence: 99%
“…parapsoriasis en plaques, considered by some experts as already CTCL. In our own clinical material, 10% of small plaque parapsoriasis (SPP) and 35% of large plaque parapsoriasis (LPP) cases developed to MF during a mean follow-up time of nine years (Väkevä et al, 2005). In advanced CTCL, malignant cells are found in lymph nodes, viscera and blood.…”
mentioning
confidence: 99%
“…[6] LPP tends to present in middle aged people with peak incidence in fifth decade with slight male preponderance. [2] Our patient had an early age of onset in the fourth decade.…”
Section: Discussionmentioning
confidence: 99%
“…In the cases we reviewed, there was a long latency between initial presentation and CTCL diagnosis. Although SPP often persists for many years, the average duration of PLC when it follows a self‐resolving course is 1·5–31 months . Many patients developed morphological changes within plaques, including induration or nodules, poikilodermatous changes and atrophic areas.…”
Section: Characteristics On Initial Presentationmentioning
confidence: 99%